Influence of metallic properties on the fracture characteristics of Al2O3/Ti/Ni‐laminated composites. Issue 6 (29th August 2022) - Liu, Quan; Xie, Ke; Xia, Hongyan; Wu, Yifan; Xu, Weiguo; Jian, Minkun; Lin, Jianping; Lu, Mi; Qiao, Guanjun
Abstract: The mutual confinement of ceramics and metals in laminated composites tends to change the original properties of ceramics and metals. In this study, two kinds of laminated composites, Al2 O3 /Ti and Al2 O3 /Ti/Ni, were prepared. Three‐point bending experiments revealed that Al2 O3 /Ti underwent brittle fracture after elastic deformation. The fracture morphology analysis revealed that the Ti in Al2 O3 /Ti became brittle due to the formation of columnar crystals. The temperature gradient perpendicular to the direction of laminations during preparation was responsible for the formation of columnar crystals. The force–displacement curves of the Al2 O3 /Ti/Ni combine the properties of elastic deformation of ceramics and plastic deformation of metals. The reason why the Al2 O3 /Ti/Ni did not fracture completely in the bending experiments is that Ni maintained the toughness, and there is a good interfacial bond among Al2 O3, Ti, and Ni. The indentation crack analysis revealed that cracks have long transverse propagation and short longitudinal propagation in both laminated composites. Finite element analysis revealed that this was due to compressive stress in the Al2 O3 layer and tensile stress in the metal layer. This compressive stress consumes the crack energy in the longitudinal direction and stops the crack in the metal layer. The brittle to ductile gradient transition among Al2 O3, Ti, and Ni, combined with the guidance of crack propagation direction by the interfacial layer, enhances the ability of Al2 O3 /Ti/Ni to resist damage.